Prediction and analysis of impact of thermal barrier coating oxidation on gas turbine creep life - Ogiriki, E. A.; Li, Yiguang; Nikolaidis, Theoklis (American Society of Mechanical Engineers (ASME), 2016)
Thermal barrier coatings (TBCs) have been widely used in the power generation industry to protect turbine blades from damage in hostile operating environment. This allows either a high turbine entry temperature (TET) to be employed or a low percentage of cooling air to be used, both of which will improve the performance and efficiency of gas turbine engines. However, with continuous increases in TET aimed at improving the performance and efficiency of gas turbines, TBCs have become more susceptible to oxidation. Such oxidation has been largely responsible for the premature failure of most TBCs. Nevertheless, existing creep life prediction models that give adequate considerations to the effects of TBC oxidation on creep life are rare. The implication is that the creep life of gas turbines may be estimated more accurately if TBC oxidation is considered. In this paper, a performance-based integrated creep life model has been introduced with the capability of assessing the impact of TBC oxidation on the creep life and performance of gas turbines. The model comprises of a thermal, stress, oxidation, performance, and life estimation models. High pressure turbine (HPT) blades are selected as the life limiting component of gas turbines. Therefore, the integrated model was employed to investigate the effect of several operating conditions on the HPT blades of a model gas turbine engine using a creep factor (CF) approach. The results show that different operating conditions can significantly affect the oxidation rates of TBCs which in turn affect the creep life of HPT blades. For instance, TBC oxidation can speed up the overall life usage of a gas turbine engine from 4.22% to 6.35% within a one-year operation. It is the objective of this research that the developed method may assist gas turbine users in selecting the best mission profile that will minimize maintenance and operating costs while giving the best engine availability.